UJI FITOKIMIA EKSTRAK BUNGA LAWANG (Illicium verum Hook.f) DAN DAYA HAMBATNYA TERHADAP Staphylococcus aureus - Rosari, Ave Regina; Duniaji, Agus Selamet; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 4 (2018): Jurnal ITEPADO - 10.24843/itepa.2018.v07.i04.p01, 2018)
This study aims to determine the levels of tannin and flavonoid compounds, as well as to determine the concentration of the extract of star anise (Illicium verum Hook.f) was most appropriate by used aquades solvent against the growth of Staphylococcus aureus. This research used experimental method with 5 kind of concentration which are 20%, 40%, 60%, 80% and 100%, each treatment was repeated 3 times to obtain 15 experimental units. The observed variables were quantitative testing of flavonoid and tannin compounds and create an inhibition zone produced by antimicrobial activity of the extract of star anise on Staphylococcus aureus. The data of this research are presented in the form of tables, figures and analyzed descriptively. The results showed that the extract contained flavonoid compounds of 0.106% and tannins of 1.018%. The extract of star anise can inhibit Staphylococcus aureus at a concentration of 40% with an average 7.03 mm inhibition zone.